Organizational Hiring Patterns, Interfirm Network Ties, and Interorganizational Imitation - Williamson, Ian O.; Cable, Daniel M. (Academy of Management Journal, 2003)
This study introduces the principles of social contagion and institutional theory to human resource management by examining the top management team (TMT) hiring patterns of Fortune 500 firms. Results provide some initial but promising evidence that social environmental factors should be incorporated into human resource management theory. Specifically, results indicate that firms hired TMT members from sources with which they shared interfirm network ties and that TMT hiring patterns were shaped by mimetic isomorphism.